SUPERVISI AKADEMIK KEPALA SEKOLAH STUDI KASUS PEMBINAAN KINERJA GURU DALAM PENGELOLA PEMBELAJARAN DI SMP NEGERI 1 SEKAYAM - Sri Prabasari, Ignatia Eni; Syukri, M.; Wahyudi, Wahyudi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe focus of this research is the principal academic supervision in order to develop teacher performance in SMP Negeri 1 Sekayam with research questions focused on: how is the planning, implementation, evaluation, and implementation of the response of teachers to the academic supervision programs, and whether the factors supporting and inhibiting academik supervision programs conducted by the principal at SMP Negeri 1 Sekayam?. To answer these questions, the researchers used descriptive research approaches and case study research. In collecting the data, the researchers as the key instruments, using the techniques of participant observation, in-depth interviews, and documents. The collected data were analyzed by using descriptive qualitative analysis . Research findings conclude that: (1) Planing academic supervision by the principal is not complete as the demands of administrative and academic supervision planning theoretical concepts. (2) The implementation of academic supervision by the principal using individual supervision techniques through class visits (3) Measure of success seen from the increasing performance of the teacher. (4) The majority of teachers responded positively to the academic supervision is carried out by the principal. (5) factors Supporting the education of human resources suggests that there is good cooperation while inhibiting factor for senior teacher sometimes appear fed up with academic supervision is carried out by the principal.Â Keywords: Academic Supervision, Principal, Guidance, Teacher Performance.